2013
DOI: 10.5812/jjm.8480
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Drug Resistance and cagA Gene in Helicobacter pylori

Abstract: Background: Currently, there are evidences for the existence of diverse strains of Helicobacter pylori with different levels of virulence. In other way, the most important reason of therapeutic failure is resistance to the antibiotics. Objectives: The aim of this study was to evaluate the relationship between H. pylori drug resistance and the presence of cagA gene. Patients and Methods: Gastric biopsy specimens were cultured for H. pylori isolation. Resistance to antimicrobial agents, including clarithromycin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…The vac A s 1 m 1/ cag A+ genotype is associated with more severe gastric diseases due to the fact that strains with this genotype cause severe inflammation with increased production of IL-1β and TNF-α, inducing inhibitors of secretion of hydrochloric acid and increase gastric pH; conditions that may favor the action of antibiotics. 56 The metronidazole resistance had relation with the presence of cag A genotype in our study, this data disagree with those reported by Khan et al 57 where they found that the absence of cag A gene contributes in the acquisition of resistance. Apparently, infected patients with vac A s 1 m 1/ cag A+ resistant strains are at increased risk of progression to more severe conditions by failure in H. pylori eradication.…”
Section: Discussioncontrasting
confidence: 99%
“…The vac A s 1 m 1/ cag A+ genotype is associated with more severe gastric diseases due to the fact that strains with this genotype cause severe inflammation with increased production of IL-1β and TNF-α, inducing inhibitors of secretion of hydrochloric acid and increase gastric pH; conditions that may favor the action of antibiotics. 56 The metronidazole resistance had relation with the presence of cag A genotype in our study, this data disagree with those reported by Khan et al 57 where they found that the absence of cag A gene contributes in the acquisition of resistance. Apparently, infected patients with vac A s 1 m 1/ cag A+ resistant strains are at increased risk of progression to more severe conditions by failure in H. pylori eradication.…”
Section: Discussioncontrasting
confidence: 99%
“…12, 36 Hence, all the samples were screened for the presence of cag A gene by PCR using two pairs of specific primers related to C-terminus and N-terminus of the cag A protein. The results indicated that all but one patient were infected with cag A-positive strains.…”
Section: Resultsmentioning
confidence: 99%
“…Korona- Glowniak et al (2019) reported that cagA and vacAs1 genotypes were present in 75 and 62.5% of MDR H. pylori strains, respectively. Ghotaslou et al (2013a) found no link between antibiotic resistance and the cagA gene. Except for metronidazole, which had a significant relationship with the cagA gene, Bachir et al (2018) found no association between vacA or cagA genotypes and drug resistance.…”
Section: Discussionmentioning
confidence: 90%